Determination of ground displacement of 25 April 2015 Nepal earthquake by GNSS precise point positioning - Lau, Nguyen Ngoc (Vietnam Journal of Earth Sciences, 2018)
The April 2015 Nepal earthquake (known as the Gorkha earthquake) occurred at 06:11:25 (UTC) on the 25th of April, with a magnitude of 7.8Mw. It was the worst natural disaster to strike Nepal since the 1934 Nepal-Bihar earthquake. Precise determination of ground displacement in this area will provide important information to better understand the structure and scope of the earthquake, contributing to faster and more accurate earthquake prediction. In this paper, we use precise point positioning to determine the displacements of 17 GNSS stations around the epicenter for the day of the earthquake. The processing results show that the common displacement direction is close to south-southwest with the largest value being approximately 2 m and the affected area being about 160 km in the southeast direction centered around the earthquake epicenter. However, a detectable GNSS signal was still observed at a station some 647 km away from the epicenter.References Akram Afifi, Ahmed El-Rabbany, 2016. Improved Between-Satellite Single-Difference Precise Point Positioning Model Using Triple GNSS Constellations: GPS, Galileo, and Beidou, Positioning, 7, 63-74. Doi.org/10.4236/pos.2016.72006. Galetzka J.,  Melgar D., Genrich J.F.,  Geng J., Owen S., Lindsey E.O., Xu X., Bock Y., Avouac J.-P., Adhikari L.B., Upreti B.N., Pratt-Sitaula B., Bhattarai T.N., Sitaula B.P., Moore A., Hudnut K.W., Szeliga W., Normandeau J., Fend M., Flouzat M., Bollinger L., Shrestha P., Koirala B., Gautam U., Bhatterai M., Gupta R., Kandel T., Timsina C.,  Sapkota S.N., Rajaure S., Maharjan N., 2015. Slip pulse and resonance of the Kathmandu basin during the 2015 Gorkha earthquake, Nepal, Science, 349, 1091-1095. Han Yue, Thorne Lay, Susan Y. Schwartz, Luis Rivera, Marino Protti Timothy H. Dixon, Susan Owen, and Andrew V. Newman, 2013, The 5 September 2012 Nicoya, Costa Rica Mw 7.6 earthquake rupture process from joint inversion of high-rate GPS, strong-motion, and teleseismic P wave data and its relationship to adjacent plate boundary interface properties, Journal of Geophysical Research: Solid Earth, 118, 5453-5466. Doi:10.1002/jgrb.50379. Ji C., K. M. Larson, Y. Tan, K. W. Hudnut, and K. Choi, 2004. Slip history of the 2003 San Simeon earthquake constrained by combining 1-Hz GPS, strong motion, and teleseismic data. Geophysical Research Letters, 31(17), L17608, 10.1029/ 2004GL020448c. Jianghui Geng, 2015. http://geoapp03.ucsd.edu/gridsphere/gridsphere?cid= Lamjung%2C+Nepal. Jianghui Geng, Chuang Shi, Maorong Ge, Alan H. Dodson, Yidong Lou, Qile Zhao, Jingnan Liu, 2012. Improving the estimation of fractional-cycle biases for ambiguity resolution in precise point positioning. Journal of Geodesy, 86, 579-589. Kouba J., 2009, A Guide to using International GNSS Service (IGS) products, Natural Resources Canada, http://igscb.jpl.nasa.gov/components/usage.html. Mahmoud Abd Rabbou, Ahmed El-Rabbany, 2015. PPP Accuracy Enhancement Using GPS/GLONASS Observations in Kinematic Mode, Positioning, 6, 1-6. Mathias Lemmens, 2015. GPS and the 2015 Gorkha Earthquake, GIM International November 2015, 29-31. Matt King, Stuart Edwards and Peter Clarke, 2002. Precise Point Positioning: Breaking the Monopoly of Relative GPS Processing, Engineering Surveying Showcase 10/2002, 33-34. Nguyen Ngoc Lau, 2009. How Accuracy GPS Precise Point Positioning can be achieved? Journal of Science and Technology Development, 12(18), 25-31. Nguyen Ngoc Lau, 2012. Monitoring the Tohoku earthquake on 11. March 2011 by using GPS Technology, International Symposium on Geoinformatics for Spatial-Infrastructure Development in Earth and Allied science, Ho Chi Minh - Vietnam,  279-289. Nguyen Ngoc Lau, 2013. Precise Point Positioning using GPS and GLONASS measurements, Journal of Geodesy and Cartography (in Vietnamese), 15, 9-17. Nguyen Ngoc Lau, Duong Minh Au, Nguyen Van Tuan, Dang Van Cong Bang, 2012. Precise point positioning using GPS and GLONASS measurements. Report of ministry-level of project B2010-30-33B2012-20-33. Nguyen Ngoc Lau, Tran Trong Duc, Duong Tuan Viet, Dang Van Cong Bang, 2010. Automatic GPS precise point processing via internet. Report of ministry-level of project B2010-30-33. Nguyen Ngoc Lau, Ha Minh Hoa, Richard Coleman, 2011. A new technique for processing GLONASS carrier phase measurements over medium length baselines using IGS products, International Journal of Geoinformatics, 7(4), 11-20. Tomokazu Kobayashi, Yu Morishita and Hiroshi Yarai, 2015. Detailed crustal deformation and fault rupture of the 2015 Gorkha earthquake, Nepal, revealed from ScanSAR-based interferograms of ALOS-2, Earth, Planets and Space, 67, 201p. UNAVCO, 2015, https://www.unavco.org/highlights/2015/nepal.html. USCG, 2015. https://earthquake.usgs.gov/research/everyone/nepal2015/. Zumberge J.F., Heflin M.B., Jefferson D.C., Wattkins M.M. and Webb F.H., 1997. Precise point positioning for the efficient and robust analysis of GPS data from large networks, Journal of Geophysical Research, 102(B3), 5005-5017.